2021
DOI: 10.1140/epjc/s10052-021-09096-7
|View full text |Cite
|
Sign up to set email alerts
|

Scalar fully-heavy tetraquark states $$QQ^\prime {\bar{Q}} \bar{Q^\prime }$$ in QCD sum rules

Abstract: Very recently, the LHCb Collaboration observed distinct structures with the $$cc{\bar{c}}{\bar{c}}$$ c c c ¯ c ¯ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…More theoretical studies considering both the meson-meson and diquark-antidiquark configurations can be found in Refs. [616,617,618,619], and there also exist some theoretical studies [620,621] taking the two heavy quark-antiquark pairs as the colored clusters.…”
Section: Compact Tetraquark Picturementioning
confidence: 99%
“…More theoretical studies considering both the meson-meson and diquark-antidiquark configurations can be found in Refs. [616,617,618,619], and there also exist some theoretical studies [620,621] taking the two heavy quark-antiquark pairs as the colored clusters.…”
Section: Compact Tetraquark Picturementioning
confidence: 99%
“…The experimental results inspired numerous theoretical discussions [39,40,[40][41][42]. The most popular interpretations are the compact tetraquark states [39][40][41][42][43][44][45][46][47][48][49][50]. Other rare interpretations, such as coupled-channel effects of double-charmonium channels [51,52], cc hybrid [53], a Higgs-like boson [54] and so on, are also proposed.…”
Section: Introductionmentioning
confidence: 81%
“…The broad structure around 6400-6500 MeV lies at the upper limit of where models predict 1S ground states to occur (e.g., Refs. [26,27]). In LHCb's Model I [1], for example, the structure is treated as a superposition of (at least) two resonances, irrespective of quantum numbers.…”
Section: B Subsequent To the Lhcb Observationmentioning
confidence: 99%